The influence of restraint and infusion on rates of muscle protein synthesis in the rat. Effect of altered respiratory function. - Preedy, V R (1988)
1. Male rats (110-140 g body wt.) were restrained by a standard laboratory technique, by wrapping in a linen towel, and subjected to a constant intravenous infusion of saline (0.15 M-NaCl) for periods of 1 or 6 h. Fractional rates of protein synthesis (ks, %/day) were estimated at the start and at the end of the infusion period, by injection of a large concentration of [3H]phenylalanine. 2. In fed and overnight-fasted rats, restraint and infusion of saline for 1 and 6 h decreased ks in skeletal muscle by 15-20% and 30-35% respectively. Plasma glucose, insulin, glucagon and corticosterone concentrations in restrained and infused rats were not characteristic of immobilization stress. 3. Restrained rats responded to nutrient administration; ks in skeletal muscle increased by 35-40% after infusion of a mixture of amino acids and glucose for 1 or 6 h, as compared with saline-infused rats. 4. Restraint and infusion for 1 or 6 h did not overtly decrease ks and kRNA (protein synthesis per unit of RNA) in hypoxaemia-sensitive tissues, such as heart and liver. Restraint and infusion in an open cage, or in a cloth of open weave, did not decrease ks in muscle after 1 h. Blood gas measurements showed that rats restrained in a linen cloth were hypercapnic and acidotic compared with rats in an open cage. 5. It was concluded that respiratory acidosis, rather than hypoxia, resulting from restraint in a linen cloth decreases muscle protein synthesis.